Peran Penyuluh Terhadap Partisipasi Belajar Kelompok Tani di Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) Kelurahan Baratan Kecamatan Patrang Kabupaten Jember - Nadhiroh, Annisa Retno; Hendrawijaya, Arief Tukiman; Himmah, Irliana Faiqotul (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
The purpose of this research is to describe the role of extension worker on farmer group learning participation in the Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) Baratan Village, Patrang District, Jember Regency. This research is a qualitative descriptive research. The technique of determining the informants used the snowball sampling technique, with informants from learning citizens, extension workers and farmer group administrators. The technique of validating research data is using extended observations, increasing persistence and triangulation of sources and techniques. The data analysis technique uses the Miles and Huberman model with the steps of collecting data, reducing data, presenting data and drawing conclusions. The results of the study show that the extension workers carry out their roles as educators, motivators and communicators well in learning at the Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) Baratan Village, Patrang District, Jember Regency. Extension workers are able to provide guidance, deliver material and provide solutions to problems experienced by learning citizens.